السرقات في المنظمات والعوامل المؤثرة فيها - حمود العنزي, سعد علي; الاتروشي, دشوار جلال (Journal of Economics and Administrative Sciences, 2007)
Employee Stealing or internal theft is considered from the passive practices that can’t be denied or be hidden, In spite of the hospital privacy as a serving organization that works 24\7 and deleing with human lives, they weren’t infallible from that kind of practice. To prevent or reduce this practice, it was important to search for the organizational and behavioral factors influencing internal thefts.      The study problem briefly is to reach the most organizational and behavioral factors influencing internal theft, in governmental hospitals in Baghdad Rusafa Health district, this was done by analyzing (20) administrative cases, of thefts occurred in the District, also a sample of (60) specialist Doctor’s opinion work, in (3) hospitals, within the Baghdad Rusafa Health district, which are Al Nu’mman, Al zahrrah, and Al kinddy hospitals, on the same subject.       Both researchers analyzed, Opportunity, Easy access to remove property, Need, Greed, Every body else doing it, Revenge due to unfair treatment by management, as behavioral factors influencing internal theft, while Leadership, Communication, Inadequate salary and payments, Goals (pressure to achieve unreasonable Goals), Inventory control, Rules controlling hospital system, as organizational factors. And they come to number of conclusions, some of them are, hospitals are as any other organizations internal theft happen inside theme, and there are number of organizational and behavioral factors, influencing more than others. Any employee in any staff position may steal, man more than woman. And reach number of recommendations to reduce the action such as inventory control, improving managers’ skills, improving the salary and payment, building solid code of conduct and ethics inside the hospitals.